Teacher’s Educational Philosophy, Teaching Style and Performance - Yazon, A D; Ang-Manaig, K (KnE Social Sciences, 2018)
A descriptive - correlational research was done to determine relationship between teacher’s philosophy, teaching style, and performance. The respondents of this study were the 33 randomly selected faculty members, constituting almost 40% of the total number of faculty members in the University. The teacher-respondents is dominated by female with the age of early fortys up to late fiftys and finished graduate studies. Further, majority of them are Assistant Professors and serving the institution for more than three decades now. More than 50% of the teacher-respondents got a Common Criteria Evaluation (CCE) and Qualitative Contribution Evaluation (QCE) points of 65 to 87 and 89% to 91% respectively. Almost 50% of the teacher-respondents are progressivists who strongly believe that teaching should prepare students for analyzing and solving the types of problems they will face outside the classroom. More than half of the respondents have somewhat individualized style of teaching which clearly means that majority of the teacher respondents focused to approximately individualized or student-centered instruction and assessment. It was found out that teacher-respondent’s performance differs significantly when they were grouped according to highest educational attainment, academic rank, and years in service. However, the data are not sufficient enough to support the existence of significant correlations between teacher’s philosophy, teaching style, and performance. The researchers concluded that when teachers were grouped according to highest educational attainment, academic rank, and years in service, significant differences between their mean performance exist. The higher the level of education, academic rank, and the longer the teacher’s length of service, the better the performance. It was also concluded that teacher’s varying philosophy and teaching styles do not predict of their performance. Keywords: educational philosophy, teachers, performance, teaching style